A Randomized, Double Blinded, Placebo-Controlled Clinical Trial of Silymarin in Ulcerative Colitis - Rastegarpanah, Mansoor; Malekzadeh, Reza; Vahedi, Homayoun; Mohammadi, Maryam; Elahi, Elham; Chaharmahali, Meghedi; Safarnavadeh, Tahereh; Abdollahi, Mohammad (Chinese journal of integrative medicine, 2015)
Objective： To evaluate the clinical efficacy of silymarin in ulcerative colitis （UC） patients. Methods： A randomized double blinded placebo-controlled clinical trial was conducted in 80 UC patients whose disease had been documented and were in remission state between September 2009 and October 2010. Patients were assigned to silymarin group （42 cases） and placebo group （38 cases） using a random number table. Either silymarin （140 mg） or placebo （lactose mono-hydrate, corn starch magnesium stearate） tablets were given once daily for 6 months along with their standard therapy. The efficacies were assessed by disease activity index （DAI）, frequency difference of the disease flare-up, and paraclinical data. Results： Ten patients （4 in the silymarin group due to nausea and 6 in the placebo group due to disease flare-up and abdominal pain） discontinued the study. An improvement in hemoglobin level （11.8± 1.6 g/dL vs. 13.4± 1.2 g/dL, P〈0.05） and erythrocyte sedimentation rate （23.7 ＋_ 11.5 mm/h vs.10.8＋ 3.2 mm/h, P〈0.05） was observed in the silymarin group but not in the placebo group. DAI significantly decreased in the silymarin group and reached from 11.3 ± 3.5 to 10.7±2.8 （P〈0.05）. Thirty-five out of 38 patients in the silymarin group were in complete remission with no flare-up after 6 months as compared to 21 out of 32 patients in the placebo group （P=0.5000）. Conclusion： Silymarin as a natural supplement may be used in UC patients to maintain remission.